The Role of UPTD Kampung Anak Negeri Kalijudan in Economic Empowerment of Children with Special Needs through Coaching and Rehabilitation - Saputra, Khrisna; Wahed, Mohammad; Iriani S, Ririt (Pascasarjana Universitas Mataram, 2025)
Abandoned Children with Special Needs (ABK) face a variety of social and economic challenges, including limited access to education, skills training, and job opportunities. This condition encourages the need for special interventions, such as coaching and social rehabilitation, to improve their independence and well-being. This article explores the strategic role of UPTD Kampung Anak Negeri Kalijudan in empowering ABK through coaching programs such as painting, batik, sewing, sports, and package chase education. The method used involves ongoing training tailored to the unique needs of crew members, aiming to develop skills, creativity, and confidence. The results show that these programs have succeeded in creating a positive impact on the economic independence of ABK, such as the sale of artworks of up to Rp 15,000,000 and personal savings of up to Rp 50,000,000. The coaching program also improves the emotional and social well-being